Spiritual Faith and Organizational Support: An Analysis of Internal and External Factors of Principals' Resilience - Aris Suharyadi; Nurtanio Agus Purwanto; Agung Purwa Widiyan; Endang Sri Budi Herawati; Yuni Astuti; Setya Raharja (Managere: Indonesian Journal of Educational Management, 2026)
Educational leaders increasingly face complex professional pressures that demand not only managerial competence but also strong adaptive and emotional capacities. This study examines how internal and external factors contribute to principals’ resilience by integrating quantitative and qualitative evidence through a mixed-methods approach. Survey data were used to identify shared perceptions regarding resilience resources, while in-depth interviews explored how principals interpret challenges and sustain leadership effectiveness in practice. The findings reveal that resilience is shaped through the interaction between adaptive meaning-making, spiritual faith, and organizational support. Emotional regulation and a clear sense of professional purpose emerged as important internal resources, while collegial collaboration and family support functioned as reinforcing external mechanisms. Spiritual practices were found to play a significant role in stabilizing emotional responses and supporting reflective decision-making during demanding situations. Rather than operating as isolated factors, these elements interact dynamically to sustain leadership stability under pressure. The integration of quantitative and qualitative findings suggests that resilience should be understood as a relational–spiritual process embedded in everyday leadership experiences. The study highlights the importance of developing leadership support systems that integrate emotional, relational, and spiritual dimensions. These findings provide practical implications for leadership development programs by emphasizing holistic resilience training that strengthens emotional regulation, collaborative organizational culture, and value-based leadership practices to support sustainable educational leadership.